A Critical Review of Visual Anthropology - Omrani, Arjang (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article aims to develop a critical overview of visual anthropology by exploring the main obstacles and pivotal challenges throughout its evolution. It explores the ongoing representational and logocentric orientations of mainstream anthropology that have caused the rejection of acknowledging audio-visual anthropology as valid academic work. Furthermore, by singling out the ocular-centric and visual realist tendencies that exist in visual anthropology, it is argued that, to some extent, it validates those criticisms and even has its roots in those representational and logocentric orientations. Within this article, a position is taken besides those who consider the 'sub-discipline' of visual anthropology as a critical approach to mainstream (social or cultural) anthropological studies. The arguments lead to the conclusion, suggesting that by distinguishing between ethnography and anthropology (Ingold: 2014 & 2017) a more diverse, creative, and comprehensive idea of audio-visual (multimodal) anthropology is probable.